How can taxes support protection of environment? - Neneman, Jarosław (W poszukiwaniu zielonego ładu, 2022)
A market economy driven by a price system, based on private ownership of the factors of production, competition, profit motives and utility maximization, can be used effectively and efficiently to protect environment. The key issue is to create the right market incentives for consumers and producers. The tax system may play an important role, on the one hand by providing funds for environmental activities, and on the other hand, no less important, although widely underestimated, by internalizing negative externalities through Pigovian tax. Market-based instruments such as taxes, fees, cap-and-trade, and subsidies allow the achievement of environmental goals in a more efficient manner (that is at a lower cost) than the direct instruments (command and control). In Poland, the market instruments are very underutilized, e.g., there is no taxation on coal used in its most environmentally harmful use, i.e., for heating houses. This is mainly due too low social awareness.